2001
DOI: 10.1074/jbc.m107726200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Export of Mammalian PERIOD Proteins

Abstract: The timing of mammalian circadian rhythm is determined by interlocking negative and positive transcriptional feedback loops that govern the cyclic expression of both clock regulators and output genes. In mammals, nuclear localization of the circadian regulators PER1-3 is controlled by multiple mechanisms, including multimerization with PER and CRY proteins. In addition, nuclear entry of mammalian PER1 (mPER1) can be regulated by a phosphorylation-dependent masking of its nuclear localization signal. Here we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 29 publications
2
72
0
3
Order By: Relevance
“…S1), which corresponds well to the consensus sequence L- (28). Whereas Leu489 mPER1 ∕Leu460 mPER2 ∕Leu399 mPER3 , Ile493 mPER1 ∕Ile464 mPER2 ∕Ile403 mPER3 , and Leu496 mPER1 ∕ Leu467 mPER2 ∕Leu406 mPER3 pack against the αC' helix of PAS-B, the C-terminal residues Leu498 mPER1 ∕Met469 mPER2 ∕ Leu408 mPER3 point to the molecule surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1), which corresponds well to the consensus sequence L- (28). Whereas Leu489 mPER1 ∕Leu460 mPER2 ∕Leu399 mPER3 , Ile493 mPER1 ∕Ile464 mPER2 ∕Ile403 mPER3 , and Leu496 mPER1 ∕ Leu467 mPER2 ∕Leu406 mPER3 pack against the αC' helix of PAS-B, the C-terminal residues Leu498 mPER1 ∕Met469 mPER2 ∕ Leu408 mPER3 point to the molecule surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanism for PER1 nuclear export has been proposed, in which the mouse PER1 nuclear localization signal (NLS, amino acids 824-851) is masked by CKIε-mediated phosphorylation of the serine cluster from amino acids 902 to 916. In addition, PER1-3 proteins contain nuclear export signals (NESs, amino acids 484-495 for mPER1) 42 . However, other studies have reported that expression of CKIε or CKIδ promotes nuclear accumulation of mouse PER1 and PER3 in COS-7 cells 16,43 .…”
Section: Nuclear Entry Of Per Regulated By Phosphorylation and Proteimentioning
confidence: 99%
“…Examination of protein localization and nuclear export is described elsewhere (Vielhaber et al 2000;Vielhaber et al 2001). Several approaches to examining the effect of phosphorylation on protein stability are available.…”
Section: Examination Of Mper2 Stability In Tissue Culture Cellsmentioning
confidence: 99%